KHARJ: KAJIAN HISTORIS PADA MASA KHALIFAH UMAR BIN ABDUL AZIZ - Farid Khaeroni (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2015)
Kharj is one of the main sources of state revenue during the caliphate of ‘Umar bin Abdul Aziz as a government to fund its management kharj assisted by Baitul Maal must meet the substance of the functions of the State. The function of the state is the first, the allocation function, can be described as the role of government to participate in directing the type of goods produced to be consumed by people and how much it is. Second, the distribution function i.e. the role of government to spread income countries and ensure the needs of the poorest communities to meet the minimum requirements. Third, stabilization function, that is, the government’s duty to maintain, especially that there is a continuity of work for all citizens, when the state cannot run these three functions, the State failing in running its government.